Diagnostic value of kappa free light chain index in patients with primary progressive multiple sclerosis – a multicentre study - Hegen, Harald; Berek, Klaus; Cavalla, Paola; Christiansen, Mikael; Emeršič, Andreja; Di Filippo, Massimiliano; Gaetani, Lorenzo; Hassler, Michaela; Leurs, Cyra; Milosavljevic, Dejan; van Pesch, Vincent; Petersen, Thor; et al. (Frontiers in Immunology, 2023)
Background: Kappa free light chains (-FLC) in the cerebrospinal fluid (CSF) are an emerging biomarker in multiple sclerosis (MS). Objective: To investigate whether -FLC index has similar diagnostic value in patients with primary progressive multiple sclerosis (PPMS) compared to oligoclonal bands (OCB). Methods: Patients with PPMS were recruited through 11 MS centers across 7 countries. -FLC were measured by immunonephelometry/ -turbidimetry. OCB were determined by isoelectric focusing and immunofixation. Results: A total of 174 patients (mean age of 5211 years, 51% males) were included. -FLC index using a cut-off of 6.1 was positive in 161 (93%) and OCB in 153 (88%) patients. Conclusion: -FLC index shows similar diagnostic sensitivity than OCB in PPMS.